The underreporting of income by self-employed workers in Spain - Diego Martinez-Lopez (SERIEs - Journal of the Spanish Economic Association, 2013)
This paper offers estimates of the underreporting of income by selfemployed workers using the Spanish household surveys over the period 2006-2009. We replicate the well-known approach by Pissarides and Weber (J Public Econ 39(1):17-32, 1989) but extending its interpretation for admitting also the concealment of income by salary workers. Our results show that the reported income by self-employed has to be increased by about 25 % to obtain the level of income which would equal the level of underreporting by employees. Our estimates are robust to changes in specification, endogeneity and non-linearities.
Keywords: D12; H26; O17; 330; Underreporting; Household surveys; Food consumption; Tax evasion